2018
DOI: 10.5588/ijtld.17.0663
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of GenoType® MTBDRsl VER 2.0 in detecting second-line drug resistance to M. tuberculosis

Abstract: The MTBDRsl VER 2.0 assay showed very high sensitivity and specificity for the detection of second-line drug resistance, suggesting it has potential for the rapid, early detection of such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Among the rrs mutations, the most common was rrs MUT1 found in 32 cases, while rrs MUT2 was present in 4 cases. These observations are comparable to the previous studies from India and South Africa [ 6 , 7 ]. We also found the mutations in eis region and the most common was eis MUT2 absent in 15 cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the rrs mutations, the most common was rrs MUT1 found in 32 cases, while rrs MUT2 was present in 4 cases. These observations are comparable to the previous studies from India and South Africa [ 6 , 7 ]. We also found the mutations in eis region and the most common was eis MUT2 absent in 15 cases.…”
Section: Discussionsupporting
confidence: 92%
“…The most common mutation detected by Genotype MTBDRsl in FQ-resistant isolates was a change at codon 94. Among codon 94 mutations, the most prominent mutation was gyrA MUT3C in 139 cases, which was comparable to the studies from South Africa, China, and India [6,7,18]. We found the rare gyrA MUT3D mutation in three cases that is absent in most of the studies, including the recent study from China [13].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Notwithstanding the fact that genotypic drug susceptibility testing has a high sensitivity and specificity but is still unable to detect all the resistance, especially in strains with novel or unknown resistance mechanisms [ 40 , 41 ]. In this review, 49 isolates with confirmed phenotypic RIF-resistance do not harbor any known mutation in the rpoB gene, which may be explained by the fact that RIF resistance-conferring mutations are present elsewhere in the rpoB gene (such as a V146F and I572F) [ 42 , 43 ], suggesting that the nature and frequency of mutations in the rpoB gene vary considerably, between different geographical regions [ 44 ], by the fact that not all the mutations are targeted by the probes used [ 45 ], or as it has been reported that molecular assays still have some drawbacks, such as product cross contamination which is a major problem leading to false positive results [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3745] This performance is also similar for genotype MTBDRsl version 2.0 in detecting mutations on rrs and eis promoter regions, predictive of phenotypic resistance to amikacin and kanamycin, and gyrA and gyrB genes for FQs [Table 1]. [4648] Compared to the Xpert® MTB/RIF platforms, the GenoType MTBDR assays are more labor intensive. They require a skilled laboratorian, adequate laboratory infrastructure compatible with at least BSL2, biosafety cabinets, three separate rooms to accommodate all steps and minimize cross-contamination risk, constant power supply, refrigerator or freezer to store reagents and centrifuges.…”
Section: Resultsmentioning
confidence: 96%